P-MN004. Multiple neurophysiologic biomarkers evaluated the pulmonary function of ALS. Issue 8 (August 2021) - Iguchi, Naohiko; Mano, Tomoo; Iwasa, Naoki; Kido, Akira; Sugie, Kazuma
Abstract : Introduction . Declining respiratory-muscle function is the primary cause of death in patients with amyotrophic lateral sclerosis (ALS). Spirometry is the most frequently used to predict hypoventilation and survival in ALS, but their cut off value cannot indicate disease prognosis. Multiple neurophysiological evaluations, which performed using diaphragmatic compound motor-action potential (DCMAP) by phrenic nerve conduction study, diaphragm thickness (DDT) by ultrasonography and new measurement system of thoracic excursion are proposed as new variable biomarkers. Methods . A total of 14 ALS patients diagnosed by El Escorial criteria were enrolled (4 females and 10 males, mean age 71.0 years, mean disease duration 29.2 months, mean body mass index ( BMI ) 19.5 kg/m 2 ). We prospectively evaluated the spirometry, arterial partial pressure of oxgen and carbon dioxide (PaO2 and PaCO2), baseline-to-peak amplitude of DCMAP, and the differences in DDT and thoracic excursion between timed maximal inspiration and maximal expiration (UMIN:000042222). We then analyzed the relationships between neurophysiological biomarkers, the respiratory-function test, and the other quantitative evaluations. Results . All patients completed the examinations with the exception of the respiratory-function test of two patients. The test–retest analysis of neurophysiologic biomarkers showed a high level of reliability. Decrease of DCMAP and DDT was detected in patients who reported no subjective dyspnea. DCMAP and DDT were found to correlate strongly with both PaCO2 and forced vital capacity (FVC); in contrast, thoracic excursion was strongly correlated to PaCO2 but not to FVC. Except for one female patient with high BMI (> 25), correlation with thoracic excursion and FVC was observed. Conclusion . Multiple neurophysiologic evaluations are reliable and reflects respiratory function. DCMAP and DDT are useful for the objective evaluations of respiratory function before the awareness of subjective dyspnea in patients with ALS.